Membangun Nalar Pengetahuan Warga Negara Melalui Buku Digital Dikalangan Mahasiswa - Jamaludin Jamaludin (Mahesa Research Center, 2020)
The purpose of this study was to see student awareness and benefits in using e-book technology to build civic knowledge in the faculty of teacher training and education at Muhammadiyah University of North Sumatra. To find out how the implementation of e-books as a scientific repertoire in civic knowledge is activated by students. This type of research is a type of qualitative research based on the phenomena that occur around the academic environment, where the research instruments used are literature study, interviews, and documentation. In this study, researchers took documents about the implementation of e-books in improving student civic knowledge, and conducted interviews with active students who were in the teaching and education faculty. The results and conclusions of this study indicate that the students 'lack of knowledge in understanding the advantages of technology is growing from day to day and one of them is an ebook, even though e-book is one of the media that can be used as a learning resource to increase students' knowledge both in terms of nature. learning and non learning